2017
DOI: 10.3389/fncir.2017.00109
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Mechanisms Governing Local vs. Global Motion Processing in Mouse Visual Cortex

Abstract: A withstanding question in neuroscience is how neural circuits encode representations and perceptions of the external world. A particularly well-defined visual computation is the representation of global object motion by pattern direction-selective (PDS) cells from convergence of motion of local components represented by component direction-selective (CDS) cells. However, how PDS and CDS cells develop their distinct response properties is still unresolved. The visual cortex of the mouse is an attractive model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Perception of visual motion is critical for animal survival, underlying behaviors such as visually guided navigation, pursuit of prey, and avoidance of threats. Although neurons selective for visual motion arise early in the visual system, extensive research in primates has shown that perception of coherent global motion independent of local motion relies on processing in specialized regions of visual cortex 1 , 2 . Although mouse visual cortical neurons are known to be well-tuned for coherent visual motion 3 , 4 , and vision plays an important role in navigation 5 , mesoscale cortical processing of coherent motion is poorly understood in the mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Perception of visual motion is critical for animal survival, underlying behaviors such as visually guided navigation, pursuit of prey, and avoidance of threats. Although neurons selective for visual motion arise early in the visual system, extensive research in primates has shown that perception of coherent global motion independent of local motion relies on processing in specialized regions of visual cortex 1 , 2 . Although mouse visual cortical neurons are known to be well-tuned for coherent visual motion 3 , 4 , and vision plays an important role in navigation 5 , mesoscale cortical processing of coherent motion is poorly understood in the mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that areas RL and A are part of the PPC in mice 15 , 16 , 17 , 18 —a key nexus of sensorimotor integration that is involved in decision making during spatial navigation, 38 the encoding of body posture, 39 global motion analysis, 40 , 41 and representations of spatial information. 42 Intriguingly, more than 50% of neurons in the RL area are multi-sensory in mice, integrating both tactile and visual sensory inputs.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our study not only yields behavioral evidence of motion integration in rodents, but also provides solid grounding for future investigations aimed at dissecting the neuronal circuits underlying integration of local motion cues into global motion percepts. In fact, as highlighted in a recent perspective (Rasmussen and Yonehara, 2017), a behavioral task involving direction discrimination of gratings and plaids is a necessary ingredient of future experiments aimed at establishing a correlational and/or causal link between patternlike responses observed in rodent visual cortex and integrated motion perception.…”
Section: Discussionmentioning
confidence: 99%